Microscopic pore structure characteristics and controlling factors of marine shale: a case study of Lower Cambrian shales in the Southeastern Guizhou, Upper Yangtze Platform, South China - Wang, Ruyue; Liu, Yuejiao; Li, Zhi; Wang, Dahai; Wang, Guanping; Lai, Fuqiang; Li, Zhihao; He, Jianhua (Frontiers in Earth Science, 2024)
A systematic study of the pore structure characteristics of Lower Cambrian shales in the southeastern Upper Yangtze Platform, was conducted using organic geochemistry, mineralogy, nitrogen adsorption, physical property analysis, and scanning electron microscopy. The results indicate that: (1) The Total organic carbon (TOC) content shows a strong correlation with quartz and clay minerals. Shales with low TOC content and rich in clay minerals primarily exhibit slit-shaped and narrow slit-like inter-clay particle pores with pore size distribution is dominated by mesopores and macropores. Shales with high TOC content predominantly feature narrow slit-like and ink bottle-shaped pores with pore size distribution dominated by micropores and mesopores. (2) Shale pore structures vary significantly under different gas content and preservation conditions. Shales under favorable preservation conditions exhibit a relatively "high porosity, low permeability, and high gas content" pattern, with well-developed organic pores and a strong pore-permeability correlation. In contrast, shales under unfavorable preservation conditions appear dense, with excessively developed fractures increasing both average pore size and local permeability. The pore-permeability correlation is weak, presenting a relatively "low porosity, high permeability, and low gas content" pattern. (3) TOC content plays a crucial role in controlling pore structure, showing overall positive correlations with pore volume, specific surface area, and porosity, and negative correlations with pore size. High TOC content enhances shale plasticity, resulting in lower pore diameters. Factors such as compaction and unfavorable preservation conditions lead to the shrinkage, collapse, and closure of some narrow pore throats, negatively impacting pore volume, specific surface area, brittleness, and fractal dimension, exhibiting a negative correlation with TOC content. (4) The pore structure of Lower Cambrian shales is complex, with fractal dimensions D1 and D2 exhibiting negative correlations with average pore size and positive correlations with TOC, specific surface area, and total pore volume. A high D1 value indicates well-preserved nanoscale pore surface structures with low complexity, suggesting minimal alteration by external fluids and better shale gas preservation. D1 serves as an indicator for shale gas content and preservation conditions. D2 shows better correlations with various pore structure parameters, making it suitable for characterizing pore structures.